2014
DOI: 10.1111/hepr.12292
|View full text |Cite
|
Sign up to set email alerts
|

Case of presymptomatic aceruloplasminemia treated with deferasirox

Abstract: Aceruloplasminemia is an autosomal recessive disease characterized by an abnormal iron metabolism. The absence of ferroxidase activity caused by mutation of ceruloplasmin leads to iron overload in the brain, liver and other organs. We report a 35-year-old man who was diagnosed with aceruloplasminemia without neurological manifestation despite the accumulation of iron in the brain and liver. To prevent the development of neurodegenerative disorder related to iron toxicity, iron depletion therapy was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Most cases originated from Japan; the geographic distribution of the cases is shown in Figure . Data on treatment and follow‐up were available in 28 original case descriptions, with follow‐up ranging from 1 week to 6 years . In 16 cases, additional information on presentation and follow‐up could be added from 14 later published articles (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Most cases originated from Japan; the geographic distribution of the cases is shown in Figure . Data on treatment and follow‐up were available in 28 original case descriptions, with follow‐up ranging from 1 week to 6 years . In 16 cases, additional information on presentation and follow‐up could be added from 14 later published articles (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, due to its insolubility in water, the method advised to patients for taking the medicine orally is quite cumbersome (Novartis 2015). In addition, reports suggest that although DFX is able to reduce both hepatic iron storage and serum ferritin concentration, it is not so efficient to treat brain iron overload (Finkenstedt et al 2010;Tai et al 2014). A recent study (Kamalinia et al 2013) has demonstrated the use of lactoferrin-DFX conjugate for efficient BBB permeation.…”
Section: Introductionmentioning
confidence: 99%
“…This early identification of aceruloplasminemia subjects enabled the exploration of effect of chelation therapy in the pre-neuro-symptomatic phase. Importantly, studies reported that these still asymptomatic individuals remained free of neurologic symptoms during follow-up lasting up to 10 years [44,46,58,59,[61][62][63][64]. Lifelong iron chelation therapy may thus potentially prevent neurologic symptoms.…”
Section: Aceruloplasminemiamentioning
confidence: 99%